Exploring the Development Prospects of Dramatherapy: A Study on the Family Therapy with the Satir Model as an Example - Zhang, Baixin (Transactions on Social Science, Education and Humanities Research, 2024)
Based on the literature review, this article summarizes that there have been a few attempts at the use of dramatherapy in family therapy, which has the potential for redevelopment. On the other hand, the Satir Model, with its mature theory and extensive practice, has shown remarkable achievements in family therapy. According to the comparative study of existing research, dramatherapy complemented the Satir Model in terms of some theories and techniques. Therefore, this study aims to explore the possibility of combining dramatherapy with the Satir Model to treat family conflicts. In conclusion, novel and thoughtful methods based on the combination of dramatherapy and the Satir Model may be constructed to deal with family conflicts to encourage clients’ involvement and to ensure their sense of security in expressing themselves freely, thereby achieving better healing effects and providing inspiration for the future application of dramatherapy and the Satir Model. This experiment also inspires the development of an independent and diverse theoretical system in the integration of dramatherapy with other healing theories and inspires the Satir Model to provide visitors with more space and create more opportunities for communication in future applications.